EFEKTIVITAS PROGRAM GENERASI BERENCANA DALAM PENCEGAHAN PERNIKAHAN DINI DI KABUPATEN MALANG - Ella Alma Damayanti; Kalvin Edo Wahyudi (Halu Oleo University, 2023)
The Planning Generation Program is carried out through two approaches, namely to teenagers through the Counseling Information Center and approaches to elderly people who have teenage children through Youth Family Development. With this goal, we increase the knowledge and skills of teenagers so that they have healthy behaviour, avoid the risks of the KRR Triad, delay marriage, have a family life plan, and create a happy, prosperous little family and become an example, model, idol and ultimate source of information for their peers. This research aims to describe the effectiveness of the Planning Generation Program in preventing early marriage in Malang Regency. The research method used is qualitative descriptive research. This research focuses on the effectiveness of the Planning Generation Program in preventing early marriage in Malang Regency by using the theoretical basis of Riant Nulgroho regarding the five correct principles for the effectiveness of policy implementation. The data collection technique in this research is through observation, in-depth interviews, and documentation review. The results of the research show that the Planning Generation Program is quite effective in preventing early marriage in Malang Regency, following Riant Nulgroho's theory, namely Right Policy, Right Implementation, Right Target, Right Environment, and Right Process. However, there are still several obstacles in its implementation.